2014
DOI: 10.1002/2014jd021994
|View full text |Cite
|
Sign up to set email alerts
|

Leader observations during the initial breakdown stage of a lightning flash

Abstract: This paper describes luminosity and leader propagation during the initial breakdown (IB) stage of a cloud-to-ground flash, beginning at 6.06 km altitude and 31.86 ms before the return stroke (RS). High-speed video (50,000 frames per s) and time-correlated electric field change (E-change) data show multiple branch ends advance concurrently in the first 6 ms of the flash; each branch begins with IB pulses and propagates first via bursts as an initial leader. Burst luminosity (pixel intensity) is directly related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(123 citation statements)
references
References 34 publications
12
110
1
Order By: Relevance
“…In the cases where the IB‐RS intervals were exceptionally short (e.g., <2 ms), it is possible that the measured VLF radiation was produced by leader processes not occurring during the IB stage. The measured IB‐RS intervals indicate the maximum duration of the leader process, as leaders can initiate either during or immediately following the IB stage [ Stolzenburg et al , ]. For a leader path length that is less than 7 km, the mean IB‐RS interval of 3.5 ms results in an average leader speed ≥2 × 10 6 m s −1 , and the median IB‐RS interval of 2.4 ms results in an average leader speed ≥3 × 10 6 m s −1 (consistent with speeds of initial leaders or the “ β ‐type” portion of leaders [ Stolzenburg et al , ; Schonland , , ]).…”
Section: Experimental Observationsmentioning
confidence: 93%
See 3 more Smart Citations
“…In the cases where the IB‐RS intervals were exceptionally short (e.g., <2 ms), it is possible that the measured VLF radiation was produced by leader processes not occurring during the IB stage. The measured IB‐RS intervals indicate the maximum duration of the leader process, as leaders can initiate either during or immediately following the IB stage [ Stolzenburg et al , ]. For a leader path length that is less than 7 km, the mean IB‐RS interval of 3.5 ms results in an average leader speed ≥2 × 10 6 m s −1 , and the median IB‐RS interval of 2.4 ms results in an average leader speed ≥3 × 10 6 m s −1 (consistent with speeds of initial leaders or the “ β ‐type” portion of leaders [ Stolzenburg et al , ; Schonland , , ]).…”
Section: Experimental Observationsmentioning
confidence: 93%
“…Wu et al [] observed that measured ratios of IB and return stroke field intensity (IB‐RS ratio) were inversely correlated to measured time delays between IB and the following return stroke (IB‐RS interval). Measured IB‐RS intervals indicate the maximum leader duration, as leaders can initiate either during or immediately following the IB stage [ Stolzenburg et al , ]. Marshall et al [] observed a similar correlation between the range‐normalized intensities of IB pulses and IB‐RS intervals.…”
Section: Initial Breakdown and Other Discharge Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rakov and Uman [3] stated that the PB process can be viewed as a sequence of channels extending in seemingly random directions from the cloud charge source with one of them evolving into the stepped leader propagating to ground. More recent studies of preliminary breakdown by Stolzenburg et al [4,5], who used high-speed video and electric field records, indicated that the PB luminosity bursts were correlated with the PB pulses in the corresponding electric field records and suggested that each PB pulse was caused by a substantial current surge traversing a channel segment of the order of hundreds of meters in length. Nag and Rakov [6], via modeling, estimated the PB pulse peak currents to be of the order of tens of kiloamperes, comparable to or even exceeding the corresponding return-stroke peak current.…”
Section: Introductionmentioning
confidence: 99%